Etika Digital dalam Kurikulum Pai: Respon Pendidikan Islam terhadap Fenomena Cyberbullying dan Hoaks - Alima, Chayara; Siti Arimbi Riyandi Putri; Herlini Puspika Sari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The phenomenon of cyberbullying and the spread of hoaxes among students has posed a significant threat to the ethics of the younger generation. Consequently, the education sector must take prudent action. The purpose of this study is to examine how the integration of digital ethics into the Islamic Religious Education (PAI) curriculum serves as an effort to prevent and address online behavioral violations. This research was conducted qualitatively using a desk study. Data were collected through documentary research of educational literature, Islamic moral values, and curriculum policies. In this analysis, a content analysis method was used to examine how Islamic concepts relate to the ethics of modern digital communication. The research indicates that the current PAI curriculum requires strengthening digital transaction materials through internalizing the principles of tabayyun (religious conduct) to combat hoaxes and the principles of akhlaqul karimah (good character) to reduce cyberbullying. PAI should not be limited to theoretical literature; instead, it should develop into a practical guide that helps people improve their digital lives. To create a safe and secure internet environment, the PAI curriculum must be aligned with critical digital literacy and the strengthening of religious character. It is hoped that this integration will provide students with a strong spiritual foundation to face the challenges of future technological disruption.